A novel scheme for denitrifying biological phosphorus removal via nitrite from nutrient‐rich anaerobic effluents in a short‐cut sequencing batch reactor. Issue 1 (3rd November 2014) - Frison, Nicola; Katsou, Evina; Malamis, Simos; Fatone, Francesco
Abstract: BACKGROUND: In this work a novel scheme was developed for nitrifying and denitrifying biological phosphorus removal via nitrite, the anaerobic co‐digestate of waste activated sludge, and the organic fraction of municipal solid waste (OFMSW) in a sequencing batch reactor (SBR). RESULTS: The on‐site available fermentation liquid of OFMSW was used to promote the biological via nitrite nutrient removal. The specific phosphorus uptake rate under anoxic conditions was, on average, 10.7 and 9.2 and mg P VSS −1  h −1 and occurred at nitrite concentrations exceeding 10 mg L −1 and up to 140 mg L −1 . Biomass was able to acclimatise and cope with such nitrite concentrations and denitrifying phosphorus‐accumulating organisms steadily developed. From the phosphorus mass balances, the phosphorus removal was mainly attributed to phosphorus‐accumulating organisms (68–71%) and partly to heterotrophic biomass growth (19–22%). CONCLUSIONS: The denitrifying biological phosphorus removal via nitrite can be successfully integrated into existing municipal plants of anaerobic co‐digestion for short‐cut nitrogen removal and enhanced biological phosphorus accumulation. © 2014 Society of Chemical Industry